The Spread of the Chikungunya Outbreak in Solok District, West Sumatera Province - 2024 - Yudi Pradipta; Elsi Novnariza; Muhammad Ilham Basgoro; Masrizal Masrizal (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Chikungunya is one of the potential diseases of the outbreak in Indonesia. It is caused by the Chik Virus and transmitted through the bite of the Aedes aegypti mosquito. The severity of symptoms ranges from mild fever to, in some cases, temporary paralysis. In early January 2024, suspected chikungunya outbreaks were reported in several villages in Solok District. The Solok District Health Office conducted an epidemiological investigation to break the chain of transmission. This study aims to describe the epidemiological characteristics of Chikungunya cases in Solok District. We conducted a descriptive study on March - June 2024. Surveillance data of Chikungunya cases were collected from West Sumatera Provincial Health Office. Data analysis was performed by using open access software Epi Info 7, R-Studio, and QGIS. A total of 134 Chikungunya cases were reported. The investigation showed that the majority of Chikungunya cases were women (63.3%), aged 18-45 years (49.54%), most of cases lived in Cupak Village (20.86%), Kinari Village (20.14%), and Muara Panas Village (20.14%), the majority cases were students (28.38%), and housewives (28.38%). The majority of cases presented with fever (95.49%) and joint pain (90.23%), and overhalf developed a rash (55.97%), and no signs of bleeding (98.51%). The epidemic curve with a propagated type indicates the possibility of multiple waves of transmission through mosquito bites. Chikungunya outbreak in Solok District shows weaknesses in early warning and rapid response in disease control. The Solok District Health Office needs to strengthening surveillance system of Chikungunya and contact tracing on the field. Keywords: Chikungunya, Mosquito, Outbreak, Vector Borne.